Examining the Mediating Role of STEM Attitudes between STEM Pedagogical Content Knowledge and STEM Intra Class Practice Self-Efficacy - Çavaş P.; Kara A.; Ş, Anagün S.; Ayar A. (International Council of Associations for Science Education, 2024)
The general purpose of this research is to examine the mediating effect of STEM attitudes between STEM pedagogical content knowledge and STEM intra class practice self-efficacy. This research was conducted in a causal design. A total of 345 teacher candidates, 261 female (75.7%) and 84 male (24.3%), were included in the research. The data was collected with the STEM Pedagogical Content Knowledge Scale (STEMPCKS), Attitude Scale for STEM Education (STEMAS) and STEM Intra Class Practice Self-Efficacy Perceptions Scale (STEMICPSEPS). Path analysis technique was used in data analysis. In addition, bootstrapping analysis was used to evaluate the significance of the mediating effect of STEM attitudes. At this point, 1000 resamples were made and lower-upper bound confidence intervals were determined. In research results, the mediating effect of STEM Attitudes was found to be significant in the relationship between STEM Pedagogical Content Knowledge and STEM Intra Class Practice Self- Efficacy. Keywords: Path analysis, STEM attitudes, STEM intra class practice self-efficacy, STEM pedagogical content knowledge.
Keywords: STEM intra-class practice self-efficacy; stem intra-class practice self-efficacy; Science; Q; STEM pedagogical content knowledge; path analysis; STEM attitudes; Theory and practice of education; Path analysis; stem attitudes; LB5-3640; stem pedagogical content knowledge; 4. Education